Protein Arginine Methyltransferase 5 Promotes Esophageal Squamous Cell Carcinoma Proliferation and Metastasis via LKB1/AMPK/mTOR Signaling Pathway - Chen, Yu-ru; Li, Hua-ni; Zhang, Lian-jun; Zhang, Chong; He, Jin-guang (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) is the eighth most common cancer in the world. Protein arginine methyltransferase 5 (PRMT5), an enzyme which catalyzes symmetric and asymmetric methylation on arginine residues of histone and non-histone proteins, is overexpressed in many cancers. However, whether or not PRMT5 participates in the regulation of ESCC remains largely unclear. Methods: PRMT5 mRNA and protein expression in ESCC tissues and cell lines were examined by RT-PCR, western blotting and immunohistochemistry assays. Cell proliferation were examined by RT-PCR, western blotting, immunohistochemistry assays, MTT and EdU assays. Cell apoptosis and cell cycle were examined by RT-PCR, western blotting, immunohistochemistry assays and flow cytometry. Cell migration and invasion were examined by RT-PCR, western blotting, immunohistochemistry assays, Wound-healing and Transwell assay. Tumor volume, Tumors and mice weight were measured in different groups. Lung tissues with metastasis foci, the number of nodules and lung/total weight were measured in different groups. Results: In the present study, the PRMT5 expression level was dramatically up-regulated in ESCC clinical tissues as well as ESCC cell lines (ECA109 and KYSE150). Furthermore, knocking down PRMT5 obviously suppressed cell migration, invasion, proliferation and cell arrest in G1 phase, and promoted cell apoptosis in ESCC cells. Meanwhile, down-regulating PRMT5 also increased the expression levels of Bax, caspase-3 and caspase-9, while expression levels of Bax-2, MMP-2, MMP-9 and p21 were decreased. Furthermore, knocking down PRMT5 could increase the expression of LKB1 and the phosphorylation (p)-AMPK expression and decrease the p-mTOR level. Additionally, over-expression of LKB1 could reveal anti-tumor effects in ESCC cell lines by inhibiting ESCC cell, migration, invasion and proliferation, and accelerating cell apoptosis. Besides, up-regulating LKB1 expression could increase the levels of Bax, caspase-3 and caspase-9, and weaken the levels of Bax-2, MMP-2 and MMP-9. Moreover, knocking down PRMT5 could weaken the tumor growth and lung metastasis in vivo with up-regulating the LKB1 expression and the p-AMPK level, and down-regulating the p-mTOR expression. Conclusions: PRMT5 may act as a tumor-inducing agent in ESCC by modulating LKB1/AMPK/mTOR pathway signaling.